PENGEMBANGAN MEDIA ROLLING BALL GAME UNTUK MEMAHAMI MATERI PADA MATA PELAJARAN IPAS KELAS IV SEKOLAH DASAR - Sabikah, Sabikah; Marhamah, Marhamah; Ayurachmawati, Puji (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2024)
This study aims to produce a valid and practical rolling ball game media on the subject of Science for Grade IV Elementary School. The type of research used is Research & Development which apllied the ADDIE stage model with five stages, namely analysis, design, development, implementation, evaluation. The subjects of this study were grade IV students of Elementary School 21 Palembang. The validity test was obtained through a validation sheet by two (2) lecturers and one (1) teacher getting an average score of 81.4% with the category "very valid". The practicality test was obtained through a student response questionnaire conducted in small groups with an average score of 93.75% with the category "very practical" and a field trial conducted by 20 grade IV students getting an average score of 94.2% with the category "very practical". It can be concluded that the rolling ball game media on plant material, the source of life on earth is valid and practical to be used for the teaching and learning process in class for grade IV students of SD Negeri 21 Palembang.